Effectiveness of myofascial release therapy for reducing low back pain in office workers: A Systematic Review & Meta-Analysis. - Huma Bukhari; Maheen.; Muhammad Mehran Haider; Waqar Ahmed; Laheem Hassan; Priyanka Ratan Kumar; Syeda Areeba Asif (International Journal of Endorsing Health Science Research, 2025)
Background: Low back pain (LBP) is a widespread and debilitating condition among office workers, primarily attributed to prolonged sitting, poor posture, and inadequate ergonomic support. Myofascial release (MFR) therapy has gained attention as a potential intervention for alleviating LBP symptoms by targeting fascial restrictions and improving musculoskeletal function. This systematic review and meta-analysis aim to evaluate the effectiveness of MFR therapy in reducing LBP among office workers by synthesizing evidence from randomized controlled trials (RCTs). Methodology: A comprehensive literature search was conducted across PubMed, PEDro, and Google Scholar to identify RCTs and quasi-experimental studies published from 2020 onward. Eligible studies focused on office workers with LBP and assessed MFR as a primary intervention. The Cochrane Risk of Bias Tool was used to assess methodological quality. Results: A total of 15 studies met the inclusion criteria, with participants having a mean age of 40 years. The meta-analysis demonstrated that MFR therapy significantly reduced LBP, yielding a standardized mean difference (SMD) of 0.75 (95% CI: 0.50, 1.00, p < 0.01). Subgroup analysis indicated that MFR was most effective when administered 2-3 sessions per week over 4-6 weeks. Furthermore, studies that combined MFR with ergonomic modifications reported greater pain reduction compared to MFR alone, suggesting a synergistic effect. Conclusion: MFR therapy is an effective intervention for reducing low back pain among office workers, demonstrating a moderate to large effect size. However, variations in treatment protocols and study quality highlight the need for high-quality, large-scale RCTs to further validate these findings and refine clinical guidelines for optimal MFR application.